Attitudes of Health Care Professionals on Parental Presence During Invasive Procedures and Resuscitation: A Cross-sectional Study in Eastern Nepal - Kafle, Shyam Prasad; Bhatta, Mukesh; Koirala, Namu; Koirala, Anupam (Birat Journal of Health Sciences, 2021)
Introduction: Trends are changing to allow parents and families to be with their child during invasive procedures. Because of the intense workload, there is a tendency to overlook the parents’ feelings. Attitudes of physicians and nurses are the common obstacles for this. Objective: To determine health care professionals’ attitudes toward parental presence during invasive procedures. Methodology: A cross-sectional study was conducted among the health professionals in the department of Paediatrics and Adolescent Medicine of a tertiary care center in Eastern Nepal. Ethical clearance was obtained from the Institutional Review Committee of the institute. Total sample size was 112 (83 nursing staff and 29 physicians). Attitudes of physicians and nursing staff towards parental presence during various invasive procedures were recorded in the predesigned proforma. Data was entered in MS Excel and analysed using SPSS version 21.0. Frequency, percentage, mean, standard deviation, chi-square test, independent t-test and one-way ANNOVA were used for data analysis at p<0.05. Results: Simple procedures like intravenous blood sampling and the simple wound repair or suture majority of the health professionals (71.1% to 79.3%) agreed for parental presence. Other major procedures including resuscitations, majority (69.0 % to 85.5%) disagreed for the parental presence. The most important factors considered was the child’s request (62.1% to 80.7%) for parental presence. The major likely reason for declining was unjustly blaming the medical staff for common/ simple complications (69.9%). Only for the simple wound repair, statistically significant differences were noted between the physicians and the nursing staff (p= 0.033) on the basis of years of experiences where the physicians preferred for the parental presence. Conclusion: Both the physicians and the nursing staff preferred not to allow the parents in the major invasive procedures including resuscitations whereas when the level of invasiveness decreased, the rate of approval increased in both the groups.